An investigation on the environmental impact of GSHP systems - Aresti, Lazaros; Christodoulides, Paul; Florides, Georgios A. (My University, 2020)
Geothermal energy, a renewable energy source, is categorized into shallow and deep applications. Shallow geothermal energy, through the use of Ground Source Heat Pumps (GSHPs) is used for space heating and cooling, where the Ground Heat Exchangers (GHEs), are used to extract or reject heat to the ground. GHE is eventually a network of pipes, with various configurations, placed either vertically or horizontally in a medium. Due to the high initial cost and long payback periods of the GSHP systems, solutions have been introduced by the scientific community. Such systems include the Thermo-Active Structures (TAS) or Energy Geo-Structures (EGS), with applications such as energy piles, diaphragm walls, shallow foundations, retaining walls, and tunnel linings. Compared to Air Source Heat Pumps (ASHPs), GSHPs achieve a better coefficient of performance (COP) resulting in savings on the consumer electricity bill. This reduction in consumed energy can be translated to less primary energy used, hence a reduction in fossil fuels used and specific environmental “harmful” gas emissions. However, it is not all black and white, and the environmental impact does not lie only on one aspect. Based on literature, such effects are presented in this study. Furthermore, a discussion on the comparison among different types of ASHPs and of GSHPs is performed.